Islamic Education Teachers' Concerns and Curriculum Use in Implementing the Merdeka Curriculum: A CBAM-Based Study in Rural Indonesia - Irawadi Irawadi; Bustanul Iman RN; Bulu Bulu (Jurnal Studi Guru dan Pembelajaran, 2026)
This research is important to understand Islamic Education teachers’ concerns and their use of the curriculum in implementing the Merdeka Curriculum in rural areas, so that educational policies can be applied effectively and in alignment with local needs. The implementation of the Merdeka Curriculum represents a significant shift toward flexible, student-centred learning in Indonesian education. However, limited empirical evidence exists regarding how Islamic Education teachers, particularly in rural contexts, experience and enact this curriculum reform. Understanding teachers' concerns and instructional practices is crucial, as ineffective implementation may result in procedural compliance rather than meaningful pedagogical change. Addressing this gap, the present study investigates the implementation of the Merdeka Curriculum by Islamic Education teachers through the lens of the Concerns-Based Adoption Model (CBAM). This study employed a qualitative case study design involving five Islamic Education teachers in rural secondary schools. Data were collected using semi-structured interviews, non-participant classroom observations, and document analysis of lesson plans, teaching modules, and assessment records. The research instruments were developed based on the Stages of Concern and Levels of Use constructs of CBAM. Data analysis was conducted through iterative qualitative coding guided by CBAM dimensions, supported by data triangulation across interviews, observations, and documents to enhance credibility. The findings reveal that teachers predominantly experienced informational and management concerns, indicating an early stage of curriculum adoption. Classroom practices were largely situated at mechanical, routine levels of use, characterized by procedural implementation rather than reflective adaptation. Although teachers reported increased student engagement, formative assessment practices remained inconsistent. These findings highlight the need for sustained, subject-specific professional development and structured mentoring to support more effective implementation of the Merdeka Curriculum in Islamic Education.